-7(x+3)-12=25+5

Simple and best practice solution for -7(x+3)-12=25+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+3)-12=25+5 equation:


Simplifying
-7(x + 3) + -12 = 25 + 5

Reorder the terms:
-7(3 + x) + -12 = 25 + 5
(3 * -7 + x * -7) + -12 = 25 + 5
(-21 + -7x) + -12 = 25 + 5

Reorder the terms:
-21 + -12 + -7x = 25 + 5

Combine like terms: -21 + -12 = -33
-33 + -7x = 25 + 5

Combine like terms: 25 + 5 = 30
-33 + -7x = 30

Solving
-33 + -7x = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '33' to each side of the equation.
-33 + 33 + -7x = 30 + 33

Combine like terms: -33 + 33 = 0
0 + -7x = 30 + 33
-7x = 30 + 33

Combine like terms: 30 + 33 = 63
-7x = 63

Divide each side by '-7'.
x = -9

Simplifying
x = -9

See similar equations:

| 13=-4+y | | 4(5-3x)=1/256 | | x^2-2y^2=3 | | 5x+2(x-3)=-2(x+1) | | 4(x+2)=3(x-5)+x | | x+9.1=1.4+9.1 | | x+3.2=7.7 | | x+1+7x=-15 | | x+9.1=4.1+9.1 | | -3-7=-4+x | | 9-(2n-6)=5-3n | | -7-3=8x+4-7x | | 1.4y=4.62 | | 9x+8-8x=13 | | X(2x+3)=(2x+5)(x-1) | | (x/50)=-11+25 | | x+12527=215+12527 | | 2+2.99999999999999999+0.1=n | | 6/5x^2+7x-70=0 | | -14+10=m-3 | | x-12527=215-12527 | | 2a+6=5a-30 | | 16(2x-1)=4(8x+9) | | 40-x=72 | | 2.561x=-12.36963 | | 2[7-5(1-n)]+5n=-6+2[6(n+1)-3n] | | 4y+y=6y-4y | | -(5x-3)-(4x-7)+6=-7(x-4)-(9x+5)+8 | | 8b+20=9b-6 | | 2x^3=384 | | (-3/-4) | | 4(x+5)=2(2x+1)+18 |

Equations solver categories